Pengaruh Air Kelapa Tua dan Cendawan Mikoriza Vesikular Arbuskular (MVA) terhadap Pertumbuhan Tanaman Sawi Hijau (Brassica juncea L.) - Tamring -; Bibiana Rini Widiati Giono; Andi Herwati (Program Studi Agroteknologi Fakultas Pertanian, Peternakan, dan Kehutanan Universitas Muslim Maros, 2023)
Mustard greens are a type of vegetable plant that is easy to cultivate, this green leafy vegetable is a plant that is resistant to rain, and can be harvested throughout the year, regardless of the season. Coconut water is a plant product that can be used to increase plant growth. The mechanism of mycorrhiza is symbiosis with plant roots through hyphae that enter the cortex cells to the endodermis of plant roots and form arbuscles filled with phosphorus. The purpose of this study was to determine the effect of doses of aged coconut water, doses of Arbuscular Vesicular Mycorrhizal fungi (AVM), and the interaction of the two which had the best effect on mustard greens. This research was conducted from March to July 2022 at Leko Hamlet, Bonto Maranu Village, Moncongloe District, Maros Regency. The research design used was a randomized block design (RBD) which was arranged in a factorial manner, where the first factor was the dose of old coconut water which consisted of 4 levels and the second factor was mycorrhizal fungi which consisted of 4 levels, each combination consisting of 3 replications, each replication consisting of 16 plants. So there are 48 plants. The results showed that the effect of the dose of old coconut water had a significant effect on the parameters of fresh root weight 7.62 g, fresh root weight per plant 105.26 g, fresh root weight 7.62 g and fresh root length 24.71 cm in mustard green plants. Meanwhile, the effect of Vesicular Arbuscular Mycorrhizal fungi (AVM) on parameters of height 21.37 cm and fresh root weight of 7.18 g in mustard greens.